The Smartphone Use and Insomnia Incidence in Health Students - lestari, hariati; Muhtar, Nafa Tryanti; Takin, Devi; Dinda; Oktaviana, Nur Widya; Israwati, Wa Ode (Community Research of Epidemiology (CORE), 2022)
The incidence of insomnia is often found in many people, especially at a young age, such as college students. The use of technology such as smartphones is suspected to be one of the causes of insomnia. This study aims to analyze the relationship between smartphone use and the incidence of insomnia in college students. This study uses a kuantitative research with a cross-sectional study design. The research was conducted on health students at various universities in Kendari City, namely FKM UHO, FK UHO, Pharmacy UHO, STIKES Mandala Waluya, ITK Avicenna and Poltekkes Kendari, class 2018-2021. The sample size of 400 respondents was taken using the proportionate stratified random sampling technique. Collecting data using an online questionnaire with google form media. Data analysis used chi-square test with 95% confidence level. Excessive smartphone use was identified in 387 (96.7%) respondents. A total of 372 (93.0%) respondents experienced insomnia. There is a relationship between smartphone use and the incidence of insomnia in health students in Kendari City (p = 0.00). Therefore, it is very necessary to limit activity and duration of smartphone use